2023
DOI: 10.3390/curroncol30030214
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Opinion on Intraoperative Radiotherapy as a Therapeutic De-Escalation Option in Older Women with Early Breast Cancer

Abstract: Background: Intraoperative radiotherapy (IORT) is a therapeutic de-escalation option in older women with low-risk early breast cancer (EBC). A qualitative study was implemented to describe EBC physicians’ points of view on IORT as a de-escalation option. Methods: Recorded face-to-face and telephone semi-structured interviews were conducted among diverse physicians from seven French comprehensive cancer centers. Interview transcripts were grouped as corpus to construct a typology. Thematic analysis was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It has been shown that longer treatment duration reduces patient confidence in therapy. 42 Therefore, the psychological state of patients with different treatment duration may lead to various effects of drugs. Nocebo effect may be reduced by increased patient-practitioner communication, which convinces the patients the effects of the drug and enhances their confidence in treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that longer treatment duration reduces patient confidence in therapy. 42 Therefore, the psychological state of patients with different treatment duration may lead to various effects of drugs. Nocebo effect may be reduced by increased patient-practitioner communication, which convinces the patients the effects of the drug and enhances their confidence in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the nocebo response rate for a treatment duration >8 weeks was higher than that for a treatment duration ≤8 weeks. It has been shown that longer treatment duration reduces patient confidence in therapy 42 . Therefore, the psychological state of patients with different treatment duration may lead to various effects of drugs.…”
Section: Discussionmentioning
confidence: 99%